Correlation between the Characteristics of Chronic Kidney Disease Patients Undergoing Hemodialysis and Erythropoietin Stimulating Agent Therapy and Hemoglobin Levels - Zainal, Dwi Trisnawati; Tamtomo, Didik Gunawan; Murti, Bhisma (Masters Program in Public Health, Sebelas Maret University, 2024)
Background: Chronic Kidney Disease is one of the deadliest diseases in the world with a high prevalence. Hemodialysis is believed to increase the survival of chronic kidney disease patients. This study aims to analyze the relationship between condition factors in patients with chronic kidney disease undergoing hemodialysis and erythropoietin stimulating agent therapy with hemoglobin levels. Subjects and Method: This research is a quantitative study with a cross-sectional study design carried out at the Madiun City Regional Hospital. Data was taken from June 1, 2022 to June 30, 2022. The population in this study were patients who received hemodialysis services and erythropoietin stimulating agent therapy. The sample was 101 patients with total sampling technique. The independent variables in this study are age, gender, duration of hemodialysis, while the dependent variable is hemoglobin level. Data collection techniques were carried out using patient medical record data. Data analysis used multiple linear regression with Stata 17. Results: The results of multiple linear regression analysis of the relationship between duration of hemodialysis, gender, age, hemoglobin levels before and hemoglobin levels after chronic kidney disease patients undergoing hemodialysis with erythropoietin stimulating agent therapy show that every 1 month increase in hemodialysis will be followed by an increase in hemoglobin of 0.02g/dL (b =0.02 CI95% 0.01 to 0.03 p=0.018). Every 1g/dL increase in hemoglobin levels before hemodialysis will be followed by hemoglobin levels after hemodialysis of 0.7 g/dL (b=0.7 CI 95% 0.6 to 0.8 p<0.001). Gender (b=-0.06 CI 95% -0.7 to 0.6 p=0.857). Age (b=-0.01 CI 95% -0.03 to 0.03 p=0.833). Conclusion: There is a positive relationship between the duration of hemodialysis and hemoglobin levels after chronic kidney disease patients undergo hemodialysis with erythropoietin stimulating agent therapy. There is no statistically significant difference between men and women, age in hemoglobin levels after undergoing hemodialysis with erythropoietin stimulating agent therapy in patients with chronic renal failure. Keywords: chronic kidney disease, hemodialysis, erythropoietin stimulating agent, hemoglobin